Effectiveness of Pivotal Response Treatment on Future Thinking and PASS Processes in Children with Autism Spectrum Disorder - Maryam Samadi; Amir Ghamarani; Salar Faramarzi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: Autism spectrum disorder is a neurodevelopmental disorder. Recent research in this area has focused on cognitive deficits such as future thinking and PASS processes (Planning, Attention, Simultaneous, and Successive) in this group of individuals, in addition to diagnostic symptoms. It seems these deficits can explain the behavioral symptoms of the disorder. Therefore, present study aimed to investigate the effectiveness of pivotal response treatment on future thinking and PASS processes of children with autism spectrum disorder.